Quality of Life (Psychosocial Domain) of Adolescents with Acute Lymphocytic Leukemia Undergoing Chemotherapy at Hematology Center in Medical City - Asmahan.Q. Mohammed, Khatam.M. Hatab (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Measurement of Quality of Life (QoL) in adolescents with acute lymphocytic leukemia and their families is to be an essential indicator of their well-being. Detecting children and families with an expected lower QoL and guiding health providers with focused treatments to enhance it will be aided by measuring multiple QoL aspects. Objectives: To assess the quality of life (psychosocial domain) of adolescents with acute lymphoblastic leukemia receiving chemotherapy. Methods: A descriptive study design was performed on adolescents with acute lymphoblastic leukemia aged 13 to 18 years. The study started from November 20, 2020 to January 1, 2022. A sample of 45 adolescents diagnosed with acute lymphoblastic leukemia who were receiving chemotherapy from a teaching hospital in Baghdad. The researchers adopted the study instrument (questionnaire) based on: Adopted quality of life scale from the world health organization scale (WHOQoL, 1995). Finding: there are significant relationships between quality of life (psychosocial domain) and socio-demographic characteristic of adolescents at p. value ≤ 0.05., except that residence and level of education are no significant relationship with the psychosocial domain. Conclusion: adolescent age from 13 to less than 18 years have moderate to low effects on psychosocial domain of the quality of life.